Differential susceptibility of human microglia HMC3 cells and brain microvascular endothelial HBEC-5i cells to Mayaro and Una virus infection - Campos, Dalkiria; Sugasti-Salazar, Madelaine; Valdés-Torres, Patricia; Galán-Jurado, Paola Elaine; Zegarra, Dalel; González-Santamaría, José (Frontiers in Virology, 2024)
Mayaro (MAYV) and Una (UNAV) are emerging alphaviruses circulating in the Americas. Earlier reports have revealed that MAYV infects different human cell lines, including synovial and dermal fibroblasts, chondrocytes, osteoblasts, astrocytes and pericytes, as well as neural progenitor cells. In this study we evaluated the susceptibility of immortalized human microglia HMC3 cells and brain microvascular endothelial HBEC-5i cells to MAYV and UNAV infection. Cytopathic effects, cell viability, viral progeny yields, and the presence of E1 and nsP1 proteins in HMC3 and HBEC-5i cells infected with several MAYV or UNAV strains were assessed using an inverted microscope, MTT assay, plaque-forming assays, and immunofluorescence or Western blot, respectively. Finally, the expression of immune response genes was analyzed using RT-qPCR. MAYV and UNAV demonstrated strong cytopathic effects and significantly reduced cell viability in HMC3 cells. Moreover, the HMC3 cells were efficiently infected regardless of the virus strain tested, and E1 and nsP1 viral proteins were detected. In contrast, only MAYV appeared to infect HBEC-5i cells, and minimal effects on cell morphology or viability were observed. Furthermore, the MAYV titer and viral protein levels were substantially lower in the infected HBEC-5i cells when compared to those of the infected microglia cells. Finally, unlike UNAV, MAYV elicited a strong expression of specific interferon-stimulated genes in microglia cells, along with pro-inflammatory cytokines implicated in the immune response. Collectively, these findings demonstrate that MAYV and UNAV are capable of infecting relevant human brain cells.